2.2 Active sites report (Scottish Archaeological Internet Reports, 2009)
This section provides information on all sites where artefactual material was recovered. It includes sites that were test pitted, shovel pitted or sites where surface collections took place. It does not include sites with surface midden that were not test pitted. There are specialist contributions on a bone comb, charcoal, coarse stone tools, metal and glass, pottery, shellfish, animal bone and fish bone.